2021
DOI: 10.1098/rspb.2021.1491
|View full text |Cite
|
Sign up to set email alerts
|

Antagonistic effects of long- and short-term environmental variation on species coexistence

Abstract: Assessing the impact of environmental fluctuations on species coexistence is critical for understanding biodiversity loss and the ecological impacts of climate change. Yet determining how properties like the intensity, frequency or duration of environmental fluctuations influence species coexistence remains challenging, presumably because previous studies have focused on indefinite coexistence. Here, we model the impact of environmental fluctuations at different temporal scales on species coexistence over a fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…The peaking of mammal richness in regions with seasonal precipitation supports the theory that intermediate levels of environmental heterogeneity promote species diversity (Adler & Drake, 2008; Tonkin et al, 2017). Ecological theory and modelling studies have indicated that temporal fluctuations in environmental conditions promote more species co‐existence than stable environments as long as the oscillations occur with intermediate and predictable frequency (Liu et al, 2021). Seasonal variability satisfies these criteria and likely promotes species co‐existence by creating temporal niches and minimising fitness differences between species with different competitive abilities, particularly in predators and herbivores (Chesson, 2000; White et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The peaking of mammal richness in regions with seasonal precipitation supports the theory that intermediate levels of environmental heterogeneity promote species diversity (Adler & Drake, 2008; Tonkin et al, 2017). Ecological theory and modelling studies have indicated that temporal fluctuations in environmental conditions promote more species co‐existence than stable environments as long as the oscillations occur with intermediate and predictable frequency (Liu et al, 2021). Seasonal variability satisfies these criteria and likely promotes species co‐existence by creating temporal niches and minimising fitness differences between species with different competitive abilities, particularly in predators and herbivores (Chesson, 2000; White et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies discussing TPCs have acknowledged the importance of actual environmental temperature on thermal performance (referred to as the probability of performance [39] or the environment-weighted performance [20]). Here, we further point out that it is crucial to understand the critical temporal and spatial environmental temperatures that affect organisms' fitness to calculate environment-weighted performance correctly.…”
Section: Discussionmentioning
confidence: 99%
“…Yet the role of temperature variability on organismal fitness is poorly understood, perhaps because temperature variation not only influences species' physiological performance [15][16][17][18], but also greatly complicates interactions among species [16,19]. More importantly, recent theoretical models have suggested that changes in the mean and variability of environmental temperature will have complex and interacting effects on species competition and coexistence [20].…”
Section: Introductionmentioning
confidence: 99%
“…In our study, the monthly fluctuating temperatures were designed to mimic the seasonal fluctuations in temperature, which did not capture the entire temperature range of the sampling sites, especially for the temperate soil (Figure S1). In addition, other intrinsic attributes of natural temperature fluctuations (such as diurnal variation and temporal autocorrelation) were not included here, which may also have profound effects on the coexistence of soil bacteria (Liu et al, 2021; Schreiber, 2021). In general, the temperature variation in our experiment is low dimensional, which alone would not be expected to support coexistence of more than a few species.…”
Section: Discussionmentioning
confidence: 99%
“…For the subtropical soil bacteria, the fluctuation‐dependent effect might hasten competitive exclusion by enlarging the differences between H‐ and L‐superior species (Figure 4b), which was opposite to that in the temperate communities. Although most of empirical studies have focused on how fluctuations in environment promote species coexistence, theoretically fluctuations in environment can also hasten competitive exclusion (Chesson, 1994; Chesson & Huntly, 1989; Liu et al, 2021; Schreiber, 2021). Specifically, in our study, the opposite fluctuation‐dependent effect found in the subtropical communities stemmed from the different performances of L‐superior species during the low‐temperature phases at the fluctuating temperatures relative to those at the constant low temperature.…”
Section: Discussionmentioning
confidence: 99%